Handbook of nephrology and hypertension - Wilcox, Christopher S; Tisher, C. Craig (Lippincott Williams & Wilkins, 2004)
Now in its Fifth Edition, this fully revised volume provides you with a concise, clinically oriented guide to the care of patients with kidney disease, hypertension, and related disorders. From a review of renal structure and guidance on evaluating renal function, to information on common renal diseases and the latest on drugs and outcomes of the major clinical trials, this handbook focuses on the types of diagnostic and treatment decisions you must make daily. The book\'s authoritative contributions from both fellows and faculty make it an indispensable quick-reference for the resident, fellow, student, or practicing clinician. NEW to the Fifth Edition... . New section on drug treatment in hypertension and renal disease offers detailed chapters on individual drug classes to guide your prescribing decisions. . New chapter on the management of anemia in renal disease details the use of erythropoietin and its analogs, iron, and other treatments for patients with chronic renal failure or end stage renal disease. . Expanded section on hypertension, diagnosis and management shows you what works and why. . More flowcharts, treatment algorithms, and diagnostic trees let you locate essential information at a glance. . Increased emphasis on the prevention of progressive vascular disease helps you counsel patients on lifestyle changes, dietary modifications, and other tools useful in the prevention of vascular disease. . Many new contributors--all noted nephrologists--assure you of only the most timely and clinically relevant perspectives available. Get rapic access to the facts you need to make the right choice for your patients with renal disease or hypertension. Order your copy today!
Keywords: nemoci ledvin; hypertenze; Nephrology; nefrologie; Hypertension; kardiologie; Kidney Diseases